Companies can lose time over conflicts: an analysis of internal indirect conflict costs - Dirrler, Phyllis; Podruzsik, Szilárd (Business: Theory and Practice, 2022)
Consequences of conflict are widely researched qualitatively, but quantitative data on the costs of conflict are lacking. This study aims to explore conflict costs by categorizing and testing them and providing preliminary quantitative data. The focus lies on internal indirect conflict costs, which are measured in terms of lost time. This research is based on self-reports of 675 survey participants, who evaluated the amount of time they spent on internal indirect conflict costs of a personal conflict. The costs are analysed in form of their explanatory power, as well as the extent to which they are affected by conflict duration and strength. All identified internal indirect conflict costs were positively correlated. The duration and intensity of the conflict affect the amount of time wasted, meaning that groups with shorter duration or weaker intensity differ from higher groups. The results indicate that conflict costs lead to remarkable costs for organizations. To remain competitive, managers need to balance the opportunities and difficulties of conflicts and carefully manage their costs. This study contributes to the unexplored research area of conflict costs and is one of the first research findings to scientifically analyse the topic.